Irish tourism : image, culture, and identity - Cronin, Michael, 1960-; O'Connor, Barbara (Cultural historian) (Tourism and cultural change, 2003)
This book is a collection of essays that examines the social, political and cultural impact of tourism on Irish society. It deals with both the historical experience of Irish tourism and with the contemporary influence of tourism on different areas of Irish life and cultural self-representation.